Energy use of methane fermentation in enterprises for the production of citric acid - Shpyakіna, Anna; Semenova, Olena; Bublienko, Natalia (My University, 2016)
Methanogenesis most appropriate appropriate, environmentally and economically beneficial process that allows you to not only solve the problem of concentrated waste water purification without their prior dilution, but also greatly enhance its efficiency and transfer to the category-generating energy by using biogas and biomass enriched with vitamins sludge.
Keywords: кафедра екології та екоменеджменту; waste water; methane fermentation; biogas; dewatered sludge; стічні води; метанове бродіння; біогаз; зневодненого осаду; сточные воды; метановое брожение; биогаз; обезвоженние осадка